PERSPEKTIF EKONOMI ISLAM TERHADAP UTANG LUAR NEGERI PEMERINTAH DALAM PEMBANGUNAN EKONOMI INDONESIA - WINDA AFRIYENIS (Maqdis: Jurnal Kajian Ekonomi Islam, 2016)
The problem of this research is how Islam regards the economy Foreign Debt Government of Indonesia and the solution according to Islamic economic perspective. This research was library research. Analysis of data using content analysis. The results of the study revealed that foreign debts are increasing in number every year. The government's foreign debt is a source of development financing is commonly done by developing countries. Indonesian government's foreign debt has been to contain the system of interest, known as riba nasi'ah, riba nasi'ah are in addition to the debt repayment required by donor countries. Thus, in their views of Islam, the government's foreign debt is currently not in accordance with the Qur'an and Hadith. Posts offer a solution formulation of the government's foreign debt in other forms of cooperation permitted under Sharia, such as Mudharabah, Musyarakah, Murabahah, Ijarah and others, can be developed as a form of external financing in the state budgets.